2015
DOI: 10.1007/s10815-015-0601-4
|View full text |Cite
|
Sign up to set email alerts
|

Independent factors influencing large-for-gestation birth weight in singletons born after in vitro fertilization

Abstract: Purpose Higher risk for birth of singletons being large for gestational age (LGA) has been revealed after in vitro fertilization (IVF) frozen-thawed embryo-transfer (FET). This phenomenon is now being investigated, since there is a speculation that these neonates could suffer from underlying epigenetic disturbances. The aim of the study was to expose independent LGA risk factors and to identify those connected to the IVF techniques. Methods Altogether, 4508 singleton pregnancies and births were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 52 publications
1
23
1
Order By: Relevance
“…These analyses indicate that frozen embryo state [4][5][6][7][8][9][10][11][12][13] is associated with an increased risk for LGA, and blastocyst embryo stage is associated with a decreased risk for SGA. The magnitude of the increase we found in the 2nd birthweight in the fresh/frozen pairs of siblings of +222 g is in accord with prior studies (+244 g 4 in an Australian population, +250 g 10 and +286 g 6 in Danish populations), and far exceeds the +81 g attributable only to an increase in parity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These analyses indicate that frozen embryo state [4][5][6][7][8][9][10][11][12][13] is associated with an increased risk for LGA, and blastocyst embryo stage is associated with a decreased risk for SGA. The magnitude of the increase we found in the 2nd birthweight in the fresh/frozen pairs of siblings of +222 g is in accord with prior studies (+244 g 4 in an Australian population, +250 g 10 and +286 g 6 in Danish populations), and far exceeds the +81 g attributable only to an increase in parity.…”
Section: Discussionmentioning
confidence: 88%
“…Prior studies have also consistently reported an excess of large-for-gestational age (LGA) birthweights among children born from frozen embryos; [4][5][6][7][8][9][10][11][12] longer embryo culture of fresh embryos has also been implicated as a potential cause of LGA [13].…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that this syndrome is genetically similar to the Beckwith-Wiedemann's syndrome in humans, which is indeed epigenetic [47]. In recent research, it was shown that BMI is an independent risk factor for being LGA; however, the investigators were unable to show a connection between BMI and transfer of cryopreserved embryos and therefore conclude that FET is also an independent risk factor for being LGA [48]. Other possible explanations could be the ART procedures itself, embryo quality or maternal factors [11,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The number of FET singletons in the studies varied from 211 (Korosec, Frangez, Steblovnik, Verdenik, & Bokal, 2016) to 55.898 (Litzky et al, 2017). The studies were conducted all over the world.…”
Section: R Es Ult Smentioning
confidence: 99%